2020
DOI: 10.1103/physrevb.101.155428
|View full text |Cite
|
Sign up to set email alerts
|

Thermal rectification and spin-spin coupling of nonreciprocal localized and surface modes

Abstract: We study the rectification of near-field radiative heat transfer between two InSb nano-particles due to the presence of non-reciprocal surface modes in a nearby InSb sample when an external magnetic field is applied and its dependence on the magnetic field strength. We reveal the spin-spin coupling mechanism of the localized particle resonances and the surface mode resonances which is substantiated by the directional heat flux in the given setup. We discuss further the interplay of the frequency shift, the pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…3 we also show the relevant part of the mean Poynting vector S tr ω describing the heat flux between the NPs as discussed in Ref. [15]. Again, it can be seen that for the "natural" dissipation the larger heat flux at the edge and corner NPs cannot be clearly seen but for the reduced damping by a factor of 10 the heat flux along the edge and corners is clearly dominating.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…3 we also show the relevant part of the mean Poynting vector S tr ω describing the heat flux between the NPs as discussed in Ref. [15]. Again, it can be seen that for the "natural" dissipation the larger heat flux at the edge and corner NPs cannot be clearly seen but for the reduced damping by a factor of 10 the heat flux along the edge and corners is clearly dominating.…”
mentioning
confidence: 62%
“…To mention a few, it could be shown that nonreciprocal nanoparticle (NP) systems show a persistent heat current [1][2][3][4], normal and anormal thermal Hall effects [5,6], giant magneto-resistance [7,8]. Furthermore, when the NPs interact with the surface modes of a nearby interface, then there can be an enhanced longrange heat transfer [9][10][11][12][13], a strong diode effect [14,15] when the interface supports non-reciprocal surface waves, and a strong directionality of heat transport and thermal emission due to hyperbolic or non-reciprocal plasmonic modes [16][17][18][19][20]. Reviews of these effects can be found in Refs.…”
mentioning
confidence: 99%
“…Based on fluctuational electrodynamics we derive the general expressions for mean Poynting vector and the heat exchange [7,8] in a general configuration of N nanoparticles in dipolar approximation with temperatures T 1 , . .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we discuss the possibility to rectify nanoscale radiative heat fluxes by means of nonreciprocal surface waves and propose a nanoscale heat flux rectifier or diode which can be controlled actively by means of externally applied fields [7]. We furthermore, reveal the spin coupling mechanism behind the observed heat flux rectification [8].…”
Section: Introductionmentioning
confidence: 96%
“…17,18 The magneto-optical material InSb has shown remarkable performance in modulating the radiative heat transfer due to the magnetically tunable properties. 5,[19][20][21][22][23] More recently, by investigating the near-field radiative heat transfer between two InSb particles, a huge anisotropic thermal magnetoresistance with values of up to 800% is achieved with a magnetic field of 5 T. 24 The GTM effect has great application significance for thermal measurement-based magnetic sensing and magnetically thermal management. However, the GTM in plasmonic structures has so far strictly relied on the magneto-optical nanoparticles made of semiconductors, like InSb.…”
mentioning
confidence: 99%